Design and Technnology Education: Whose design, whose education and why? - Keirl, Steve (Design and Technology Education: An International Journal, 2006)
This paper seeks to demonstrate the significant, if not essential, place of design in our lives and in the technological world. Further, it contends that such a significant presence warrants a role for design in the general education of all students in two principal ways. In one way, it presents design as necessary to the integrity of Technology Education. In another, as a result of this necessary integrity, it argues a case for the key role of Design and Technology (D&T) Education as a core component of any ethically defensible curriculum of a state education system. The case presented is not limited to any particular society or educational jurisdiction.